2020
DOI: 10.1111/chso.12380
|View full text |Cite
|
Sign up to set email alerts
|

Doing ethnographic method with babies – Participation and perspective approached from the floor

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(70 reference statements)
0
3
0
1
Order By: Relevance
“…Regarding everyday objects, it is impressive to see the number of objects that children are confronted with [12]. Technical objects and technology are part of children's lives.…”
Section: Children and Technical Objectsmentioning
confidence: 99%
“…Regarding everyday objects, it is impressive to see the number of objects that children are confronted with [12]. Technical objects and technology are part of children's lives.…”
Section: Children and Technical Objectsmentioning
confidence: 99%
“…In the wake of Alma Gottlieb’s criticism, a growing number of childhood researchers have begun to reflect on the fact that the field, while nominally covering children of all ages, has paid scant attention to infants (e.g., Brownlie & Leith, 2011; Oswell, 2013). Scholars who do study infants freely admit to its difficulties, as their subjects’ lives seem so abstruse that it leads only to unreliable observations (Elwick et al, 2014; Orrmalm, 2020a, 2020b).…”
Section: (Re)navigating Children’ Agency Ethnographically With Imagin...mentioning
confidence: 99%
“…To resolve these problems, the authors suggested several innovative methods drawing from other researchers. Besides that, there are also inspirational ethnographic studies investigating infants' perspectives through their body movements, in which the researcher plays a crucial role in making interpretations of the 'messy' behaviors (Orrmalm, 2020a(Orrmalm, , 2020b). Yet, just as what I will do below, these methods still rely heavily on adults' (researchers or caregivers) experiences with and perspectives of infants, which may not necessarily reflect the children's 'real' thoughts.…”
Section: Challenges Of Approaching Infants and Children With Developm...mentioning
confidence: 99%
“…Exempelvis har begreppet "barns röster" kritiseras utifrån att det tenderar att synliggöra barn som har en röst i traditionell mening (talat språk) medan grupper av barn som saknar sådan röst blir osynliggjorda, exempelvis yngre barn (t.ex. Orrmalm, 2020) eller barn med olika funktionsnedsättningar (t.ex. Key och Tisdall, 2012).…”
Section: Barns Deltagande Och Delaktighet I Forskningunclassified